New engineered phenolic biosensors based on the AraC regulatory protein. Issue 6 (19th September 2018) - Frei, C S; Qian, S; Cirino, P C
Abstract: Customized transcription factors that control gene expression in response to small molecules can act as endogenous molecular biosensors and are valuable tools for synthetic biology. We previously engineered the Escherichia coli regulatory protein AraC to respond to non-native inducers such as D-arabinose and triacetic acid lactone. Those prior studies involved the construction and screening of individual 4- or 5-site saturation mutagenesis libraries, followed by iterative rounds of positive- and negative fluorescence-activated cell sorting (FACS). Here we describe an improved screening platform and the isolation of several new and potentially useful AraC variants that respond to vanillin and salicylic acid. To increase throughput and reduce total screening time, selection steps were added to the sorting workflow. Two different site-saturation libraries and a random mutagenesis library were pooled together and >10 8 variants were subjected to iterative FACS and selection in search of variants responding to a panel of compounds. The new phenolic-sensing variants show responses >100-fold over background and are highly specific towards their target compound. The isolation of these variants further demonstrates the potential for engineering the AraC transcriptional regulatory protein for molecular sensing and reporting, and our improved screening system should prove effective in designing similar biosensors.